Ultrasound and pathology of the main bile duct - Croci, Fabio; Cluzet, Oscar; Cresseri, Aída; Petersen, Federico; Nuchovich, Mauricio (Cirugía del Uruguay, 1982)
The authors analyze the efficacy of ultrasonography in the diagnosis of the biliary tract path ology; in a series of 104 hospital patients. In every case the results were confirmed by preoperative C holangiography and surgery. The present study shows the reliability of ultrasonography in patients with presumed or proved pathology of the biliary tract. The positive diagnosis of a surgical pathology of the biliary tract, be it tumoral or due to lithiasis, seems to be the most remarkable use of ultrasonography. At the same time emphasis is made upon its great usefulness as a reliable method in the diagnosis of a jaundiced patient.